FoodCloud: Stimulating Kindness Towards Making the World a Fairer Place - One Step at a Time - Caffrey, Eamonn; Brady, Liam; Flynn, Sean; Higgins, Jane; McKenna, Ellen Marie; Newman, Julie; Nolan, Paul (Senate Hall, 2020)
The case follows the journey of Irish social enterprise FoodCloud as it rises to the extensive task of reducing global food waste by providing an environmentally-sensitive, socially-responsible, and economically-viable alternative. From its humble beginnings as a socially oriented technology start-up pioneered by Aoibheann O'Brien and Iseult Ward, FoodCloud has utilised both its innovative technology platform and an innate ability to form successful partnerships as the strategy to pave its international expansion. The case illustrates the sizable challenges in leading on social enterprise initiatives. The organization's development path is described to provide a good sense of the growth trajectory that emerged for FoodCloud during its young history to date. Notably, FoodCloud have developed strategic capabilities that are arguably, critical to the survival and success of any social enterprise entity.
Keywords: entrepreneurial strategy|innovation|internationalisation|leadership|partnership|purpose|social enterprise|strategic alliance|sustainability|technology platform